2022
DOI: 10.1002/anie.202207089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Specific Activity of M−N−Cs and the Intrinsic Activity of Tetrapyrrolic FeN4 Sites for the Oxygen Reduction Reaction

Abstract: MÀ NÀ C electrocatalysts are considered pivotal to replace expensive precious group metal-based materials in electrocatalytic conversions. However, their development is hampered by the limited availability of methods for the evaluation of the intrinsic activity of different active sites, like pyrrolic FeN 4 sites within FeÀ NÀ Cs. Currently, new synthetic procedures based on active-site imprinting followed by an ion exchange reaction, e.g. Zn-to-Fe, are producing single-site MÀ NÀ Cs with outstanding activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…Pyrrolic FeN4 sites, however, display a different trend, the -OH and -NH2 ligands strengthens the *OH binding, placing pyrrole FeN4 with -NH2 close to the top of the volcano. Very recently, it has been suggested that pyrrolic Fe sites show a low catalytic activity; [74] our DFT study therefore suggests that their activity could be increased through axial ligand coordination, such as pyrrole or -NH2. DFT reveals here for the first time that the type, or lack, of axial ligand has a large impact on *OH binding energy for both pyrrolic and pyridinic sites.…”
Section: Resultsmentioning
confidence: 58%
“…Pyrrolic FeN4 sites, however, display a different trend, the -OH and -NH2 ligands strengthens the *OH binding, placing pyrrole FeN4 with -NH2 close to the top of the volcano. Very recently, it has been suggested that pyrrolic Fe sites show a low catalytic activity; [74] our DFT study therefore suggests that their activity could be increased through axial ligand coordination, such as pyrrole or -NH2. DFT reveals here for the first time that the type, or lack, of axial ligand has a large impact on *OH binding energy for both pyrrolic and pyridinic sites.…”
Section: Resultsmentioning
confidence: 58%
“…However, relatively poor volumetric activity of SACs precludes them from many applications in industry due to the desire for reaction intensification. In order to improve the catalytic performance, it is important to increase the active site density of SACs and understand how site density influences the overall activity of the catalyst. Although the metal center(s) is presumed to be the active site in many of the reactions mentioned above, the active site density does not equal the amount of metal present in the catalyst because some metal centers are either inactive or buried and inaccessible to the reacting species . In fact the situation becomes even more complex as the M–N/Cs potentially contain more than one type of active sites.…”
Section: Introductionmentioning
confidence: 99%
“…N 1s XPS spectrum shows that the N‐containing species of Fe 2 DAC are composed of pyridinic N, pyrrolic N, graphitic N and oxidized N (Figures S19 and S20, Supporting Information). Among them, the pyrrolic N occupies the highest ratio, which may promote the 4 e − transfer for electrochemical oxygen reduction (Table S3, Supporting Information) [35, 36] . These results unveil that DACs with dual‐metal Fe centers can be realized by direct pyrolysis of COF with well preorganized bimetallic sites.…”
Section: Resultsmentioning
confidence: 81%
“…Among them, the pyrrolic N occupies the highest ratio, which may promote 4 e À transfer for electrochemical oxygen reduction (Table S3, Supporting Information). [35,36] These results unveil that DACs with dualmetal Fe centers can be realized by direct pyrolysis of COF with well preorganized bimetallic sites. To the best of our knowledge, this is the first attempt of fabricating DAC from COF with specific coordination sites.…”
Section: Synthesis and Characterization Of Fe 2 Dacmentioning
confidence: 82%